Preschool Teachers’ Educational Perspectives in the Implementation of the Reggio Emilia Approach: Take a kindergarten in Singapore as an example - Chen Chen; Mohd Nazri Bin Abdul Rahman (P3I UMSurabaya, 2024)
With advancements in technology and societal development, early childhood education curricula are continuously evolving to meet societal demands. Globally, an increasing number of preschools are adopting the Reggio Emilia approach and a “child-centered” educational philosophy. This study aims to explore the practical application of the Reggio Emilia approach in a preschool in Singapore. A qualitative research design was utilized, and data were collected through open-ended, semi-structured interviews with three participants. Snowball sampling was employed to recruit preschool teachers for the study. The findings indicate that teachers are inspired by the Reggio Emilia philosophy and attempt to incorporate it into their teaching practices in various ways. However, limitations such as resource constraints and a lack of parental understanding hinder full implementation of the approach. Thus, establishing a strong support system that addresses teachers’ actual needs is essential for the successful implementation of the Reggio Emilia curriculum.